2014
DOI: 10.1007/s10530-014-0740-z
|View full text |Cite
|
Sign up to set email alerts
|

How can an invasive grass affect fire behavior in a tropical savanna? A community and individual plant level approach

Abstract: Some invasive grasses have been reported to change fire behavior in invaded plant communities. Urochloa brizantha is an aggressive invasive grass in the Brazilian Cerrado, an ecosystem where fire is a common disturbance. We investigated the effects of U. brizantha on fire behavior in an open Cerrado physiognomy in Central Brazil. Using experimental burnings we compared fire behavior at both the community and the individual plant level in invaded (UJ) and non-invaded (NJ) areas burned in July. We also assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
1
48
0
6
Order By: Relevance
“…Monitoring natural regeneration until some of the secondary savanna characteristics reach old‐growth savanna values and subsequently removing trees to avoid the thickening of the vegetation (Brudvig, ) may be the most adequate restoration strategy because it has relatively low costs and at least maintains the old‐growth savanna structure and part of its animal and plant diversity, which requires an open habitat to survive (Abreu et al., ; Durigan & Ratter, ; Murphy, Andersen, & Parr, ; Veldman et al., ). The reintroduction of fire to secondary Neotropical savannas may be equally effective to avoid vegetation thickening, but further studies are needed to optimize this management practice because exotic grasses change fire behaviour (Gorgone‐Barbosa et al., ) and may have undesirable effects on secondary savannas.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring natural regeneration until some of the secondary savanna characteristics reach old‐growth savanna values and subsequently removing trees to avoid the thickening of the vegetation (Brudvig, ) may be the most adequate restoration strategy because it has relatively low costs and at least maintains the old‐growth savanna structure and part of its animal and plant diversity, which requires an open habitat to survive (Abreu et al., ; Durigan & Ratter, ; Murphy, Andersen, & Parr, ; Veldman et al., ). The reintroduction of fire to secondary Neotropical savannas may be equally effective to avoid vegetation thickening, but further studies are needed to optimize this management practice because exotic grasses change fire behaviour (Gorgone‐Barbosa et al., ) and may have undesirable effects on secondary savannas.…”
Section: Discussionmentioning
confidence: 99%
“…Exotic invasive species (hereafter exotic species) can alter community‐level flammability in two main ways. First, the exotic species may possess functional traits, such as substantially different moisture content, volatile organic compounds or retention of dead material, which make it either more or less flammable than the native species in the recipient community, therefore changing community‐level flammability (Brooks et al., ; Gorgone‐Barbosa et al., ; Livingston & Varner, ; McGranahan, Engle, Miller, & Debinski, ). Second, invaders can increase, decrease or change the distribution and continuity of fuel loads (Berry, Wevill, & Curran, ; Brooks, ; Gorgone‐Barbosa et al., ; McGranahan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the exotic species may possess functional traits, such as substantially different moisture content, volatile organic compounds or retention of dead material, which make it either more or less flammable than the native species in the recipient community, therefore changing community-level flammability (Brooks et al, 2004;Gorgone-Barbosa et al, 2015;Livingston & Varner, 2016;McGranahan, Engle, Miller, & Debinski, 2013). Second, invaders can increase, decrease or change the distribution and continuity of fuel loads (Berry, Wevill, & Curran, 2011;Brooks, 2008;Gorgone-Barbosa et al, 2015;McGranahan et al, 2013). Most examples of invasion-induced changes to fire regimes have focussed on the effect of a single invading species and have shown that the invader has increased the flammability of the community (D'Antonio & Vitousek, 1992); but invaders can also reduce plant community flammability (Brooks et al, 2004;Gorgone-Barbosa et al, 2015;Livingston & Varner, 2016;McGranahan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of Urochloa spp. in Cerrado can change fire behavior by affecting fire intensity, maximum temperature and flame height (Gorgone-Barbosa et al 2015).…”
Section: Study Speciesmentioning
confidence: 99%